2017
DOI: 10.2105/ajph.2017.303985
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Worker Support for Disadvantaged Patients With Multiple Chronic Diseases: A Randomized Clinical Trial

Abstract: Objectives. To determine whether a community health worker (CHW) intervention improved outcomes in a low-income population with multiple chronic conditions. Methods. We conducted a single-blind, randomized clinical trial in Philadelphia, Pennsylvania (2013–2014). Participants (n = 302) were high-poverty neighborhood residents, uninsured or publicly insured, and diagnosed with 2 or more chronic diseases (diabetes, obesity, tobacco dependence, hypertension). All patients set a disease-management goal. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
260
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 189 publications
(262 citation statements)
references
References 29 publications
1
260
0
1
Order By: Relevance
“…Thus, patients should be equipped with the right skillsets for self-care. Various studies identified the need to facilitate self-management and provide adequate support, for example, through community programmes (59)(60)(61)(62)(63)(64)(65)(66). Although healthcare providers might have provided selfmanagement guidelines and support to polyclinic patients, our study found that patients' practices were still affected by their daily activities involving work and the community, as well as their beliefs and physical condition.…”
Section: Key Findings and Recommendationsmentioning
confidence: 66%
“…Thus, patients should be equipped with the right skillsets for self-care. Various studies identified the need to facilitate self-management and provide adequate support, for example, through community programmes (59)(60)(61)(62)(63)(64)(65)(66). Although healthcare providers might have provided selfmanagement guidelines and support to polyclinic patients, our study found that patients' practices were still affected by their daily activities involving work and the community, as well as their beliefs and physical condition.…”
Section: Key Findings and Recommendationsmentioning
confidence: 66%
“…A face-to-face intervention with CHW's could offer advantages for rural populations compared to telephone support modalities. In several studies, diabetes self-management interventions used a combination of in-person and telephone visits in accordance with patient preferences (Allen et al, 2011;Kangovi et al, 2017;Palmas et al, 2015;Tang et al, 2014). The convenience of either in-home or telephone visits also improved retention compared to travel required for DSME interventions (Lepard et al, 2015).…”
Section: Rn Telephone Managementmentioning
confidence: 99%
“…In addition, the effects of diabetes self-management interventions on lowering hospital admissions and emergency department visits have been inconsistent (Begum, Ozolins, & Dower, 2011;Lorig et al, 2013;Sacks et al, 2017). A recent randomized controlled trial using a CHW intervention demonstrated significant decreases in hospital admissions but nonsignificant improvements in PAM scores (Kangovi et al, 2017).…”
Section: Rn Telephone Managementmentioning
confidence: 99%
“…29 As a result of the implementation research undertaken to adapt the intervention to a new setting, the research team was able to launch both single-and multicenter randomized controlled trials (RCTs) to test the effectiveness of the new intervention. 30,31 Combined, these studies led to the creation of the Penn Center The implementation research examples highlighted here provide insights into how implementation science can support social prescribing's transition from innovative pilot work to sustainable primary care practice. Many other opportunities exist for new research to be conducted in this rapidly evolving field.…”
Section: Payment Modelsmentioning
confidence: 99%